SODIUM NITROPRUSSIDE USE IN THE TREATMENT OF SEVERE HYPERTENSION PRE-ECLAMPSIA AND ECLAMPSIA - Gotuzzo Herencia, Eduardo (2015)
6 and 2 Eclampsia Pre-Eclampsia: 8 carriers patient Pre-eclampsia were reported. Both groups Severe Hypertension (BP average: 216/146 mmHg). They were administered sodium nitroprusside infusion, reducing blood pressure to acceptable levels (average PA: 150/105 mmHg) without significant side effects on the mother and fetus. The number of patients reported is small and can not draw definitive conclusions, but this study shows that the use of sodium nitroprusside is possible to control hypertension toxemia of pregnancy at reasonable levels and thus reducing morbidity and mortality in this entity. Another interesting fact of this publication lies in being the first time that the use of sodium nitroprusside in hypertension of pregnancy toxemia reported.